Magnetocaloric properties of cluster glass compound Pr2Ni0.95Si2.95. (August 2019) - Pakhira, Santanu; Mazumdar, Chandan; Ranganathan, R.
Abstract: In this work, we report the magnetocaloric properties of a hexagonal intermetallic compound Pr2 Ni0.95 Si2.95 that exhibits spin cluster glass behaviour below 3.3 K. At lower temperature, the compound undergoes magnetic field induced metamagnetic transition beyond 5 kOe applied field value as inferred from the temperature dependence of magnetization at various fields as well as isothermal magnetization measurements. The temperature dependence of magnetic entropy change ( − Δ SM ) has been calculated from the magnetization data and the maximum value is found to be 7.9 J/kg-K for a magnetic field change of 70 kOe. Interestingly, although the compound does not undergo any long range magnetic ordering, it exhibits considerable magnetocaloric effect in a temperature region much above the spin freezing due to the presence of short range magnetic correlation that persists up to much higher temperature. The suppression of short range interaction with the application of magnetic field has been argued to be responsible for such magnetic entropy change and adiabatic temperature change over a large temperature scale. Highlights: Magnetocaloric properties of cluster glass compound Pr2 Ni0.95 Si2.95 is reported. Considerable MCE is obtained in this low moment rare-earth system. Magnetic ground state found to be fragile and undergoes metamagnetic transition. Maximum value of MCE is observed at a temperature higher than spin freezing. Presence of short range interactions above Tf is responsible for large MCE.